Kinetics of Tofu Pulp as Copper Metal Adsorbent on the Waste of the Silver Craft Industry - Indah, Dahlia Rosma; Hatimah, Husnul (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Liquid waste originating from the silver crafts industry is heavy metal waste that is dangerous for the surrounding environment, one of which is copper (Cu). Copper is a heavy metal that can have toxic effects on human health. Based on these problems, processing is needed to reduce the pollutants produced. One of the technologies used is adsorption using a natural adsorbent that is efficient and easy to obtain, namely tofu dregs. Adsorption using tofu dregs is because tofu contains protein. This protein has the ability to absorb amino acids which form two charged ions (zwitter ions). Toxic metals can be bound to proteins as metallothionein. This research aims to determine the efficiency of using tofu dregs as an absorbent for copper metal (Cu) and to determine the effect of contact time and adsorption isotherms on copper metal adsorption. 1 gram of tofu dregs was used with 25 ml of waste and then contacted with a magnetic plate stirrer at varying times of 30, 60, 90, 120 and 150 minutes. The concentrations of all copper metals were analyzed using an Atomic Absorption Spectrophotometer. Next, each copper metal content was calculated using a copper metal standard calibration curve. Identification using an Infrared Spectrophotometer showed that the tofu dregs waste in this study contained the functional groups -OH, N-H (stretching), C-H (aliphatic), C=O, -OH (bending vibration), and C-O. From the research it was found that the copper metal content in the sample was 19.5979 ppm. The optimum contact time for copper metal adsorption is 120 minutes, which results in an optimum adsorption efficiency for copper metal, namely 54.88%. The isotherm equation that corresponds to the adsorption of copper metal using tofu dregs waste is the Freundlich isotherm with a Kf value of 0.072 L/g and a 1/n value of 2.366. This shows that the adsorption of copper metal occurs in a multilayer layer on the surface of the tofu dregs adsorbent, which illustrates the occurrence of physical adsorption. Tofu dregs waste is an effective adsorbent for reducing copper metal levels in silver craft waste.